Genetic Improvement of Milk Quantity and Milk Quality in Holstein Friesian Cattle by Selection - Anneke Anggraeni (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2012)
Milk yield and milk quality are essential in determining the development of national dairy industry. Domestic fresh milk is largely produced by Holstein Friesian  cows. There is a wide variation of the genetic ability of cows to produce milk or bulls to transmit milk, thus giving the opportunity for the improvement of milk production trait through selection. Milk yield as one of the quantitative traits, in the genetic evaluation, is estimated based on a breeding value. Breeding value can be estimated accurately through appropriate selection methods and by considering various non-genetic factors influencing milk production. This paper focuses the discussion on milk selection methods, which are very commonly done in dairy cattle. To produce superior dairy breeding cattle, selection for the bulls were done by progeny testing method, whereas selection for cows were commonly by individual selection method and their siblings. A number of internal environment factors should be considered in the genetic evaluation of milk production, through the development of appropiate correction factors, thereby increasing the accuracy of the estimated breeding values. The quality of milk especially milk protein contents, in the future, will get more attention from consumers. Therefore, selection should be directed also to improve milk protein components. The existence of major genes controlling on milk protein contents is expected to be the effective way in increasing milk protein yield in domestic HF cow. Selection of superior breeding dairy cattle in producing high milk protein contents is done through the identification of polymorphism of milk protein genes, providing casein and whey family genes. Key words: Holstein Friesian, selection, milk yield, milk protein